Evaluating the effectiveness of palm oil as bio-aviation fuel on Indonesia aviation industry: Reducing emissions and opportunity of having carbon allowances (Journal of Social Economics Research, 2025)
This study investigates the economic feasibility and environmental benefits of integrating Palm Kernel Oil (PKO)-based bio-aviation fuel (BAF) into Indonesia’s domestic aviation sector. Drawing on data from major flight routes and applying a Hydroprocessed Esters and Fatty Acids (HEFA)-based emissions model, the analysis calculates CO2 emission reductions of 74%–84% compared to conventional fossil jet fuel, providing strong evidence of its environmental potential. The cost-revenue model, combined with ARIMA-based price forecasting, reveals that despite isolated instances of positive profitability, such as on the Jakarta–Medan route in 2023, PKO-based BAF remains economically unviable under current market conditions, largely due to the persistent cost gap with fossil jet fuel. Price forecasts indicate sustained PKO price levels between USD 1170–1193 per metric ton and carbon credit prices averaging USD 77 per metric ton through 2026, suggesting limited opportunity for natural market correction. Sensitivity analysis identifies that carbon prices would need to rise by up to 182% to achieve breakeven, emphasizing the urgent need for robust policy measures, including minimum carbon pricing, fiscal incentives, and investment in supply chain efficiencies to make BAF adoption viable. This research advances the sustainable aviation fuels (SAF) literature by integrating emissions modeling, economic analysis, and market forecasting in the context of an emerging economy, providing a novel contribution to discussions on aviation decarbonization. The findings offer actionable insights for policymakers, industry stakeholders, and researchers aiming to design effective interventions and shape the future of sustainable aviation in Indonesia and similar emerging markets.